1991
DOI: 10.1109/3.90008
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-current analysis of InGaAs-InGaAsP multiquantum well separate-confinement lasers

Abstract: An analysis of the threshold behavior of long-wavelength ( lambda =1.55 mu m) multiquantum well separate-confinement lasers with InGaAs wells and quaternary ( lambda g=1.3 mu m) barriers is presented. Using the effective mass approximation and Fermi statistics for carriers, an approximately logarithmic dependence of optical gain on carrier density for quantum well lasers with one confined electron state is predicted theoretically. This prediction is verified by measured threshold currents of broad-area lasers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Figure 1 shows that four resonances provide a good fit to the semiconductor gain spectrum [6]. We found that spatially resolving the carrier lifetime and incorporating carrier diffusion was essential in achieving a physically realistic number of lasing modes.…”
Section: Methodsmentioning
confidence: 91%
“…Figure 1 shows that four resonances provide a good fit to the semiconductor gain spectrum [6]. We found that spatially resolving the carrier lifetime and incorporating carrier diffusion was essential in achieving a physically realistic number of lasing modes.…”
Section: Methodsmentioning
confidence: 91%
“…We call this device a 1G (1 st Generation) Si laser. The threshold current density of the 1G Si laser was 1.1 kA/cm 2 , which was as large as that of a near-infrared semiconductor laser fabricated from InGaAsP, which is a direct-transition-type compound semiconductor [7]. A dressed-photon is a quasiparticle representing a coupled state between a photon and an electron at the nanoscale [8].…”
mentioning
confidence: 99%
“…It is also the tool of choice for engineers to model devices such as lasers and photodetectors. [13][14][15][16][17][18] Also, its use is widespread in the calculation of transmission coefficients [19][20][21] and quasibound state lifetimes, 22,23 with application to the modeling of resonant tunneling devices.…”
Section: Introductionmentioning
confidence: 99%